Risk Assessment of Dam-Breach Flood Under Extreme Storm Events - Lin, Xiajing; Huang, Guohe; Wang, Guoqing; Yan, Denghua; Zhou, Xiong (Frontiers in Environmental Science, 2021)
In recent years, as a result of the increasingly intensive rainfall events, the associated water erosion and corrosion have led to the increase in breach risk of aging dams in the United States. In this study, a hydrodynamic model was applied to the inundation simulation under three hypothetical extreme precipitation-induced homogeneous concrete dam breach scenarios. All hydraulic variables including water depth, flow velocity, and flood arriving time over separated nine cross-sections in the Catawba River were calculated. The hypothetical simulation results illustrate that the impact of Hurricane Florence's rainfall is far more severe over the downstream of hydraulic facilities than that of the Once-in-a-century storm rainfall event. Despite Hurricane Florence's rainfall observed in Wilmington had not historically happened near the MI Dam site, the river basin has a higher probability to be attacked by such storm rainfall if more extreme weather events would be generated under future warming conditions. Besides, the time for floodwaters to reach cross-section 6 under the Hurricane Gustav scenario, is shorter than that under the Once-in-a-century rainfall scenario, making the downstream be inundated in short minutes. Since the probability can be quantitively evaluated, it is of great worth assessing the risk of dam-break floods in coastal cities where human lives are at a vulnerable stage.